3149 Embedding Implementation Science Within a Translational Health Sciences PhD: Educating Future Scientists to Bridge the Gap Between Research, Practice and Policy. (27th March 2019) - Corcoran, Mary; McDonald, Paige; van der Wees, Philip; Schlumpf, Karen; Weaver, Jennifer
Abstract : OBJECTIVES/SPECIFIC AIMS: Determine the effectiveness of a curriculum designed to teach doctoral students to use implementation science theories, models and frameworks in optimizing scientific, social, political, cultural and organizational impact METHODS/STUDY POPULATION: Analysis of Integrated Final Projects across three cohorts of doctoral students (N=30) to identify sub-disciplinary knowledge integration and application. RESULTS/ANTICIPATED RESULTS: Integrated Final Projects indicate that the integration of IS, Program Theory and Research design within semester two yields application of integrated, sub-disciplinary knowledge to research design, identification of mechanisms of action and the address of barriers and facilitators to implementation of findings. Future analysis will be conducted to determine the degree to which dissertations reflect a similar level of sub-disciplinary integration and focus on implementation within the appropriate service setting. DISCUSSION/SIGNIFICANCE OF IMPACT: Training future translational researchers to understand and use implementation science theories, models and frameworks can potentially result in narrowing the science-to-service gap.